Incidence of inferior alveolar nerve sensory deficit and intra-operative nerve encounters after advancement of retrognathic mandible – A cross-sectional survey study - Suresh Vyloppilli; Annamalai Thangavelu; Sankar Vinod Vichattu; Nithin Kumar; Fahad Ahmad; Shermil Sayd (Indian Journal of Dental Research, 2022)
Aims and Objectives: The aim of the current cross-sectional study was to conduct a survey among the oral and maxillofacial surgeons of South India regarding their experiences of incidence of inferior alveolar nerve (IAN) neurosensory deficit after bilateral sagittal split osteotomy (BSSO) for correction of mandibular retrognathism and to assess the intra-operative nerve encounters and its effect on the inferior alveolar neurosensory deficit (NSD), 6 months post-operatively. Materials and Methods: A self-administered questionnaire (SAQ) was prepared using Google Forms (Google Inc.) and sent to the prospective participants through various social media outlets such as Facebook, WhatsApp groups etc., of the maxillofacial surgery specialty for a period of 3 months. SAQ from surgeons with more than 5 years of experience in orthognathic surgery were included. Results: The incidence of NSD post-BSSO advancement surgery from 859 cases after 6 months was 15.1% (130). After splitting the mandible, the IAN was seen in the proximal fragment in 472 sites and needed dissection. The nerve was transected and neurorrhaphy was carried out in 26 sites. A Chi-square test was used to analyse the qualitative variables. The IAN was not visible post-osteotomy in 140 sites and in the distal fragment in 1080 sites. These groups had decreased incidence of NSD. The NSD was significantly higher in cases where the nerve was transected and sutured, P value <0.001 as compared with the other nerve status, followed by the nerve in the proximal fragment needing dissection. Conclusion: The IAN status intra-operatively can be assumed to have a significant role in persisting NSD.